The Anatomy of Job Polarisation in the UK - Andrea Salvatori (Institute for the Study of Labor (IZA), 2015)
This paper presents new evidence on the evolution of job polarisation over time and across skill groups in the UK between 1979 and 2012. The UK has experienced job polarisation in each of the last three decades, with growth in top jobs always exceeding that in bottom ones. Overall, top occupations have gained over 80% of the employment shares lost by middling occupations. The decline of middling occupations is entirely accounted for by non-graduates who have seen their relative numbers decrease and the distribution of their employment shift towards the bottom of the occupational skill distribution. The increase at the top is entirely accounted for by compositional changes, as a result of the increase in the number of graduates since the 1990s. Employment has not polarised for graduates, but has become less concentrated in top occupations, especially in the 2000s. The paper also documents that job polarisation has not been matched by wage polarisation across the occupational distribution in any decade and discusses how these new findings relate to the existing evidence for the US and to the prevailing technology-based explanation for job polarisation. Overall, the importance of occupational changes between skill groups and the performance of occupational wages over time cast doubts on the role of technology as the main driver of polarisation in the UK. In particular, the evidence suggests that supply-side changes are likely to be important factors in explaining why high-skill occupations continued to grow in the 2000s even as they stalled in the US.
Keywords: J21; J23; J24; O33; 330; job polarisation; wage inequality; occupational mobility; routine employment; skill biased technological change